Diet and physical activity interventions in Black and Latina women with breast cancer: A scoping review - Pichardo, Margaret S.; Sanft, Tara; Ferrucci, Leah M.; Romero-Ramos, Yaideliz M.; Cartmel, Brenda; Harrigan, Maura; Velazquez, Ana I.; Fayanju, Oluwadamilola M.; Winer, Eric P.; Irwin, Melinda L. (Frontiers in Oncology, 2023)
Background: A growing number of lifestyle interventions are being developed to promote weight loss and adoption of a healthful lifestyles among breast cancer survivors; yet Black and Latina women remain underrepresented. Purpose: We performed a scoping review of the available peer-reviewed literature to describe and compare the content, design, methods, and primary outcomes of current diet and/or physical activity (PA) interventions after a breast cancer diagnosis among Black and Latina women. Methods: We queried PubMed, EMBASE, CINAHL, MEDLINE, and Clinicaltrials.gov up to October 1, 2022, to identify all randomized controlled trials of diet and/or PA after diagnosis of breast cancer with a majority (>50%) of Black or Latina participants. Results: Twenty-two randomized controlled trials were included in this review (five efficacy, twelve pilot, five on-going). Nine trials were among Latinas (two diet, four PA, and three diet/PA), six among Blacks (two PA and four diet/PA) and seven included both populations (five PA and two diet/PA), all of which examined different endpoints. Two of the five efficacy studies achieved their a priori outcome (one diet trial improved short term dietary intake; one PA trial achieved clinically significant improvements in metabolic syndrome score), both in Latinas. Eight pilot trials intervened on both diet and PA and three of them found favorable behavioral changes. Three (two for Latinas and one for Blacks) out of the eight diet and PA pilot trials and three (all for Latinas) efficacy trials incorporated a culturally focused approach (i.e., traditional foods, music, Spanish content, bicultural health coaches, spirituality). Overall, four trials, including one efficacy trial, had one-year follow-up data, with three finding sustained behavior change. Electronic/mobile components were incorporated in five trials and one involved informal care givers. Most of the trials were geographically limited to the Northeast USA (n=8, NY, NC, DC, NJ) and Texas (n=4). Conclusions: Most of the trials we identified were pilot or feasibility studies and of short duration, demonstrating the need for large randomized controlled efficacy lifestyle interventions among Black and Latina breast cancer survivors. Culturally tailored programing was limited but is an important component to incorporate in future trials in these populations.